Catalytic transfer reductive cleavage of azo compounds to amines using chitosan-supported formate and zinc. (1st January 2013) - Han, Y.Q.; Yu, X.H.; Xu, L.; Song, H.; Yan, G.F.; Ma, X.J.; Zhen, Y.Z.
A convenient method for the cleavage of azo derivatives to the corresponding amines using chitosan-supported formate as hydrogen donors in conjunction with zinc is described.